Testicular cells in hybrid water buffaloes (Bubalus bubalis) - Bongso, Tuan Ariffeen; Abdullah, Mohamad Hilmi; Basrur, P. K. (Elsevier, 1983)
Meiotic chromosome behaviour and testicular histology were studied in water buffaloes (Bubalus bubalis) including two river (Murrah), two swamp and three F1 (Murrah cross swamp) hybrids aged between two and two and a half years, from testicular biopsies obtained by an open surgical method. Meiotic preparations revealed spermatogonial metaphases, pachytene, diplotene, diakinesis, first and second meiotic metaphases and spermatozoa in all three types of buffalo. Chromosome sets ranging from 22 to 26 (most frequent, 24 and 25) with many cells carrying univalent, bivalent and multivalent configurations were observed in hybrids, whereas the meiotic cells in the Murrah and swamp showed chromosome sets exclusively of 25 and 24 (bivalents) respectively. Histological examination of the hybrid testis revealed a large proportion of degenerating spermatocytes and abnormal spermatids in the process of spermiogenesis suggesting that the various synaptic associations leading to unbalanced gametes may be responsible for the degenerating germ cells in the hybrids. The unbalanced meiotic products will probably lead to selection against such spermatozoa or early embryos after fertilisation. Due to a large percentage of germinal epithelial cells in F1 hybrids being wasted, the fertility of backcross and F2 generations will be subnormal.